A consensus for occupational health management of healthcare workers infected with human immunodeficiency virus, hepatitis B virus, and / or hepatitis C virus. Issue 3 (20th May 2017) - Ishimaru, Tomohiro; Wada, Koji; Smith, Derek R.
Abstract : Occupational health management plays an important role in the prevention of provider‐to‐patient transmission in healthcare workers infected with human immunodeficiency virus (HIV), hepatitis B virus (HBV), and/or hepatitis C virus (HCV). Therefore, the Japan Society for Occupational Health's Research Group on Occupational Health for Health Care Workers has proposed a consensus for the management of healthcare workers infected with HIV, HBV, and/or HCV based on recent evidence for each concerned group. The consensus recommends that: (1) employers in medical institutions should establish a policy of respecting the human rights of healthcare workers, management strategies for occupational blood exposure, and occupational health consultation; (2) occupational health staff should appropriately assess the risk of provider‐to‐patient transmission of HIV, HBV, and / or HCV infection and rearrange their tasks if necessary. When conducting risk assessment, occupational health staff should obtain informed consent and then cooperate with the physician in charge as well as infection control experts in the workplace; (3) healthcare workers infected with HIV, HBV, and/or HCV should disclose their employment to their treating physician and consult with their doctor regarding the need for special considerations at work; and (4) supervisors and colleagues in medical institutions should correctly understand the risks of HIV, HBV, and HCV infection and should not engage in any behavior that leads to discrimination against colleagues infected with HIV, HBV, and/or HCV.